Influence of ligand architecture on oxidation reactions by high-valent nonheme manganese oxo complexes using water as a source of oxygen - Barman, Prasenjit; Vardhaman, Anil Kumar; Martin, Bodo; Wörner, Svenja; Sastri, Chivukula V.; Comba, Peter (Angewandte Chemie. International edition, 2015)
Mononuclear nonheme MnIVO complexes with two isomers of a bispidine ligand have been synthesized and characterized by various spectroscopies and density functional theory (DFT). The MnIVO complexes show reactivity in oxidation reactions (hydrogen-atom abstraction and sulfoxidation). Interestingly, one of the isomers (L1) is significantly more reactive than the other (L2), while in the corresponding FeIVO based oxidation reactions the L2-based system was previously found to be more reactive than the L1-based catalyst. This inversion of reactivities is discussed on the basis of DFT and molecular mechanics (MM) model calculations, which indicate that the order of reactivities are primarily due to a switch of reaction channels (σ versus π) and concomitant steric effects.
First published: 29 December 2014
Gesehen am 30.07.2020